PELATIHAN PENYUSUNAN ARGUMENTASI HUKUM DALAM OPTIMALISASI LEGAL ADVICE PADA BAWASLU - Purnamasari, Andi Intan; Supriyadi, Supriyadi; Moh Yunus , Nursiah; Awaliyah , Awaliyah (CV. Era Digital Nusantara, 2023)
This study focuses on efforts to improve the ability of human resources through the form of training in producing legal argumentation as one of the strengthening skills of Bawaslu members in Donggala district. Legal Argumentation is essentially made to answer certain issues. This issue generally arises from the client. Therefore, a legal argumentation must be made in a focused, systematic, and proportional manner. Legal argumentation usually only consists of 3-5 pages. For this reason, legal argumentation must focus only on the issue in question, not discussing matters outside of it. Legal argumentation must also be systematic so that the description is easy to understand. There is no standard format for a Legal Argumentation, but at least an LO consists of: (1) the case, (2) identifiable and relevant legal basis, (3) legal opinion, and closed with (5) conclusion, which includes suggestions or recommendations.